2015
DOI: 10.3389/fsurg.2015.00029
|View full text |Cite
|
Sign up to set email alerts
|

Results from a First-in-Human Trial of a Novel Vascular Sealant

Abstract: BackgroundSuture hole bleeding from synthetic grafts presents a hemostatic challenge. The designs of many vascular sealants are not optimal (non-adherence to wet surfaces, excessive swelling, inflexible). PreveLeak™ (formerly ArterX®) is a polyaldehyde–bovine serum albumin-based sealant whose efficacy, safety, and performance were evaluated in this first-in-human study.Materials and methodsA prospective, single-arm, multicenter study was performed in patients undergoing open vascular reconstructions with prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Due to the higher molecular weight of polyaldehyde relative to glutaraldehyde, leaching of the reactive species from PreveLeak is much less than that from BioGlue. 366 PreveLeak elicits only minimal inflammation, compared to BioGlue. The adverse events in patients treated with PreveLeak have been reported to be consistent with those commonly observed in patients undergoing surgical procedures.…”
Section: Protein Based Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the higher molecular weight of polyaldehyde relative to glutaraldehyde, leaching of the reactive species from PreveLeak is much less than that from BioGlue. 366 PreveLeak elicits only minimal inflammation, compared to BioGlue. The adverse events in patients treated with PreveLeak have been reported to be consistent with those commonly observed in patients undergoing surgical procedures.…”
Section: Protein Based Adhesivesmentioning
confidence: 99%
“…To circumvent the toxic effects caused by glutaraldehyde, PreveLeak exploits an alternative form of aldehyde, polyaldehyde. Due to the higher molecular weight of polyaldehyde relative to glutaraldehyde, leaching of the reactive species from PreveLeak is much less than that from BioGlue . PreveLeak elicits only minimal inflammation, compared to BioGlue.…”
Section: Representative Examples Of Adhesivesmentioning
confidence: 99%
“…11 The use of biological tissue adhesives and surgical sealants of various types is well established in many fields of surgery, including otorhinolaryngology. 23 Recent research has evaluated the use of surgical sealants to prevent pharyngocutaneous fistula. In the context of the support of a suture repair, the need for tensile strength may be of less importance; however, sealing properties are key.…”
Section: Resultsmentioning
confidence: 99%
“…This sealant is proven to work in a bloody or dry environment, whereas other sealants, such as cyanoacrylate, require drier conditions. 23 Recent research has evaluated the use of surgical sealants to prevent pharyngocutaneous fistula. An animal study compared the use of 3 tissue glues (a fibrin adhesive, a synthetic adhesive, and a protein-based albumin glutaraldehyde adhesive) and platelet-rich plasma applied over a sutured pharyngotomy with a control group (suture repair only).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,5 Use of conventional synthetic grafts such as polytetrafluoroethylene [PTFE] grafts further exacerbate NHB. 3,[5][6][7][8] Early research demonstrated that using sutures with a small needle-to-suture (N:S) diameter ratio (eg, 1:1) reduces the discrepancy between the diameter of the needle hole and the diameter of the suture filling it, thereby significantly reducing NHB. 8,9 The ROLENE suture with HEMO-SEAL technology (HEMOSEAL suture) represents the latest breakthrough in suture technology.…”
Section: Introductionmentioning
confidence: 99%